Avaliação do efeito antitumoral in vitro de nanocápsulas de núcleo lipídico de tretinoína sobre células de adenocarcinoma de pulmão, linhagem A549 - Schultze, Eduarda (2013)
Retinoid derivatives and analogs have been widely studied as antitumor agents due to their effects on cell proliferation and differentiation. Tretinoin (TT), also known as retinoic acid is a retinoid derivative that has been used as an adjuvant in the treatment of acute promyelocytic leukemia with excellent rates of remission. This compound has antiproliferative activity in various tumor types. However, non small cell lung cancer in general exhibit strong resistance to the effects of TT, which may be related to the deficiency in the cellular up-take of TT in that cell type. A strategy to enhance the antiproliferative activity of TT is to increase the cellular internalization of the compound through carriers such as liposomes or other vesicles or nanospheres or nanocapsules. Here we evaluated TT lipid-core nanocapsules (TT-LCNC) for their power to inhibit growth, induce apoptosis and interfere with the cell cycle of lung adenocarcinoma, A549 cell line, which is resistant to treatment with TT. The results showed that TT-LCNC was able to overcome the cellular resistance to treatment with TT, reducing cell viability and inducing apoptosis, upregulation of P21 and cell cycle arrest in G1 phase.